2009
DOI: 10.3727/096368909x471314
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Mesenchymal Tissue Cells Inhibit Dendritic Cell Differentiation of Peripheral Blood and Amnion Resident Monocytes

Abstract: Cells derived from the amniotic membranes of human term placenta have drawn much interest for their characteristics of multipotency and low immunogenicity, supporting a variety of possible clinical applications in the field of cell transplantation and regenerative medicine. We have previously shown that cells derived from the mesenchymal region of human amnion (AMTC) can strongly inhibit T-lymphocyte proliferation. In this study, we demonstrate that AMTC can block differentiation and maturation of monocytes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
108
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 64 publications
8
108
1
4
Order By: Relevance
“…Human-and mousederived av-MSCs improved bleomycin-induced lung fibrosis in a mouse model [36]. In vitro, av-MSCs suppressed Tlymphocyte proliferation [37,38], and prevented differentiation of monocytes into dendritic cells [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human-and mousederived av-MSCs improved bleomycin-induced lung fibrosis in a mouse model [36]. In vitro, av-MSCs suppressed Tlymphocyte proliferation [37,38], and prevented differentiation of monocytes into dendritic cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…av-MSCs are also known to secrete a variety of immunomodulatory factors [13,37,[39][40][41][42]. The application of Cdm from av-MSCs reduced progression of lung fibrosis in a mouse model [43] and led to favorable clinical outcomes when treating tendon and ligament injuries in horses [44].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multipotent MSCs have also been isolated in placental tissues, including the amnion and chorion layers of the amniotic membrane,21, 22, 23, 24 and these amniotic membrane derived stem cells have demonstrated the ability to regulate immune cells though secretion of various immunomodulatory cytokines 25, 26, 27, 28…”
Section: Introductionmentioning
confidence: 99%
“…Little information is available about the effector molecules from human amniotic mesenchymal stromal cells responsible for this suppression, but these molecules may include prostaglandin E2, tumor necrosis factor γ, interleukin 10, transforming growth factor β, and soluble human leukocyte antigen G. [34][35] Studies with 1-way lymphocyte reactions have shown that human amniotic mesenchymal stromal cells do not induce human T-cell proliferation. 32 In the present study, we showed that human amniotic mesenchymal stromal cells may induce inhibitory effects on allogeneic and xenogeneic T cells in 2-way mixed lymphocyte reactions.…”
Section: Discussionmentioning
confidence: 83%
“…[29][30][31] In addition, human amniotic mesenchymal stromal cells may modulate immune cell activities and may be transplanted across major histocompatibility complex barriers. [32][33] Amniotic cells may suppress T-cell proliferation because of cell-cell contact and secrete of cytokines. Little information is available about the effector molecules from human amniotic mesenchymal stromal cells responsible for this suppression, but these molecules may include prostaglandin E2, tumor necrosis factor γ, interleukin 10, transforming growth factor β, and soluble human leukocyte antigen G. [34][35] Studies with 1-way lymphocyte reactions have shown that human amniotic mesenchymal stromal cells do not induce human T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%